Migration and livelihood of rural households in Nigeria (2023)
With agriculture being the main source of livelihood, migration has posed severe constraints, thus hampering the livelihood of many households. This research focused on the effects of migration on the livelihood of rural households in Nigeria. Descriptive statistics, Probit and Tobit regression models were the analytical tools employed. Most of the households were male-headed and two-thirds of the rural households had members who had migrated for at least six months. Internal migration was the predominant type of migration while rural households were found to have a low level of livelihood. Age, education, household size, type of employment, land access, type of dwelling, migrant status and physical assets were significant in determining livelihoods of rural households. Thus, lessening the rural-urban divide in the rural areas through public-private partnerships in terms of innovations to support and expand the livelihood possibilities of rural households at all levels of governance should be prioritized.